Research on the Impact of upgrading of consumption structure on energy intensity under the background of urban and rural dual economy. Issue 1 (March 2020) - Li, Yan; Li, Yuan; Chen, Tao; Hu, Ying-Ying
Abstract: Based on the current situation of dual economic structure of urban and rural areas in China, this paper takes urban and rural areas as two independent research objects, and constructs the panel threshold regression model of consumption structure upgrading on energy consumption intensity. The results show that the upgrading of regional urban residents' consumption structure has double threshold effect on energy intensity, and the upgrading of urban residents' consumption structure has a restraining effect on energy intensity. With the upgrading of per capita income, it first decreases and then increases; the upgrading of regional rural residents' consumption structure has a double threshold effect on energy intensity, the upgrading of rural residents' consumption structure will significantly inhibit the energy intensity when the per capita income of residents is in the maximum range. In addition, under the threshold of per capita income, compared with rural areas, the upgrading of consumption structure of urban residents has a more prominent effect on the inhibition of energy intensity.